An investigation into the ability of riders to obtain an ideal dressage position - Tabor, G.; Randle, H.; Ezra, R.; Brown, L.; Mackenzie, K.; Langfjord-Clare, E.; Williams, C.; Clarke, A.; Parker, K. (DCA Report; Nr. 044, 2014)
The correct riding position is considered impactful for rider injury risk reduction and the welfare of the horse. A balanced rider position may reduce injury risk caused by rider falls and also help avoid musculoskeletal injuries to both the rider and horse. Considering the importance placed on rider position, research is sparse with rider position teaching methods being based on tradition rather than scientific research. The purpose of this study was to evaluate riders` ability to obtain a correct dressage position whilst sat on a dressage saddle, placed on a saddle horse, through comparison with their actual position. The correct position was considered to be with the shoulder, hip and heel vertically aligned (ESHH). Markers were placed on the lateral aspect of the right shoulder, hip and ankle joints. The subjects were instructed to mount the saddle horse and sit in the saddle in a position that they would maintain when riding a dressage test. The riders did not receive any verbal or visual feedback on their position. Images were taken from the right side, recorded using a digital camera. Rider position was analysed using Image J™ software where the distances between the shoulder and the vertical line, and the ankle and the vertical line were measured. The vertical line was drawn with the mid-point over the lateral aspect of the hip joint. Fifteen novice/non-competitive (NC) riders were compared with fifteen advanced/competitive riders (C). All riders (n=30) positioned their ankle in front of the vertical line and 27 (90%) riders had their shoulders behind the vertical line. There was no significant difference in the distance between the shoulder and vertical in the two groups (NC: mean 5.47±3.00 cm vs. C: 4.02±3.43 cm; t28=0.17; P>0.05) and the ankle and vertical (NC: mean 8.71±5.52 cm vs. C: 8.68±5.16 cm; t28=0.98; P>0.05). It is therefore suggested that rider experience does not influence the position maintained. The saddle may have had more influence on rider position rather than the experience of the rider. Analysis of each subjects` position in alternative styles of saddles would be the logical progression of this study. LP: The position of the rider is important to reduce the risk of injury to both the horse and the rider. When sat in a dressage saddle, all riders had their legs in front of the vertical and most had their shoulders behind the vertical. Further study is needed to help better understand the effects of rider position and therefore improving the welfare of the horse.